The effect of Vigna unguiculata mulching on growth and yield performance of aerobic rice (AERON 1) / Hamdiyana Hamdan - Hamdan, Hamdiyana (Faculty of Plantation and Agrotechnology, 2019)
This research was carried out to evaluate the effect of mulching application on growth and yield performance of an aerobic rice at the greenhouse Universiti Teknologi Mara (UiTM), Melaka Campus Jasin. The objectives of this study is to study the effectiveness of Vigna unguiculata mulching on yield and growth performance of aerobic rice. There were 2 treatments along with 5 replications were used in this experiment. The treatment consist of Vigna unguiculata mulching, and no mulching (control) and each of it consist five replications. Each of aerobic rice were planted in a single pot and each pot were applied 20 gram of mulching which act as a treatments. AERON1 variety was chosen in this experiment because of rapid growth and this experiment was conducted for 100 days. Vigna unguiculata mulching has the highest mean number for plant height (116.37cm), number of tiller (9.55), and plant biomass (83.108g). The aerobic rice plant that consist of mulching has better result in growth performance for all parameter included plant height (P=0.004), number of tillers (P=0.004), and also plant biomass (P=0.002). As for yield, the number of panicle, grain weight, and % of empty grain have the highest mean for the treatment with mulching. The % of fill grain has the highest mean for treatment without mulching. The result showed that all yield parameter analysis have no significant different, which the number of panicle (P=0.083), grain weight (P=0.127), and % of empty and filled grain (P=0.597). Lastly, mulching application was effective and showed it had significant different on growth performance, but on yield performance there was no significant. The application of mulching can be used by farmer as it would give benefit in terms enhancing the plant growth and yield.